2014
DOI: 10.1002/maco.201307278
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium on the corrosion of hot-dip galvanized steel in chloride containing environments

Abstract: In this work, three different hot-dip galvanizing alloys ZnAl0.2, ZnAl5, and ZnAl2Mg2 were tested in non-standardized salt spray tests. In those nonstandardized salt spray tests, samples were exposed to different pH values, calcium and magnesium ions. The corrosion products formed on the alloys in different conditions were analyzed with XRD and Raman spectroscopy. Additionally, the corrosion behavior of the samples was investigated by studying cross-section cuts with SEM. By analyzing the corrosion products fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The better corrosion performance of ZnMgAl is predominately found at acidic to neutral pH. It was also found that zinc‐based coatings were rather heavily corroded when Ca 2+ ions were applied whereas all zinc‐based coatings showed the same good corrosion performance in magnesium chloride solution . Surface pH is crucial for the formation of corrosion products, especially for simonkolleite and hydrozincite.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The better corrosion performance of ZnMgAl is predominately found at acidic to neutral pH. It was also found that zinc‐based coatings were rather heavily corroded when Ca 2+ ions were applied whereas all zinc‐based coatings showed the same good corrosion performance in magnesium chloride solution . Surface pH is crucial for the formation of corrosion products, especially for simonkolleite and hydrozincite.…”
Section: Introductionsupporting
confidence: 90%
“…Yet another model states that Mg 2+ buffers the surface of ZnMgAl to a pH value that supports the formation of a protective layer of simonkolleite and hydrozincite. The theories, which are currently under discussion have in common that the oxygen diffusion is somehow retarded due to the formation of dense corrosion products . A main contribution to the enhanced corrosion protection of ZnMg(Al) is attributed to the formation of layered double hydroxides (LDH) by co‐precipitation of the corresponding ions .…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect is observed on pure Zn coatings when low quantities of magnesium are present in the corrosive agent (e.g. : MgCl 2 ) . Magnesium cations also play a role in inhibiting the oxygen reduction on steel, which contributes to a self‐healing effect at the cut‐edge of galvanized steel samples .…”
Section: Introductionmentioning
confidence: 63%
“…An equilibrium governed by the surface chemistry is rapidly reached after relatively short periods of spray application. When HDG and the alloy materials were subjected to large volumes of solutions while maintaining the pH, a stronger effect was observed, particularly in the alkaline region [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of permanent wetness discussed above, it explains the huge difference between HDG and Zn-Mg(-Al) in conditions of the neutral salt spray test (NSST), where the latter material shows up to 20-fold lower mass loss [2][3][4][5]27].…”
Section: Discussionmentioning
confidence: 99%